2005
DOI: 10.1111/j.1470-6431.2005.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint analysis of consumer preferences for roasted peanut products in Haiti

Abstract: This study evaluated Haitian consumers' preferences for three attributes of roasted peanuts: form (dry-roasted vs. honey-roasted), country of origin (Haiti vs. USA) and price (lowest vs. most common vs. highest). A sample of 199 respondents from three locations near Port-au-Prince revealed that price was overwhelmingly the most important attribute, although three well-differentiated consumer segments were identified: the largest (44% of the sample) based strictly on price; a second (29%) distinguished by prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 2 publications
1
20
0
1
Order By: Relevance
“…Price, method of processing, and information on preservatives accounted for 34.54% of the respondents' purchase intents contributing 13.16%, 11.15%, and 10.23%, respectively (Table 2). Purchase intent decreased with an increase in price in accord with previous findings on fruits and vegetables (Van der Pol & Ryan, 1996), traditional cheeses (Souza Monteiro & Lucas, 2001), beef (Mesias, Escribano, de Ledesma, & Pulido, 2005), roasted peanuts (Nelson et al, 2005) and soybean oil (Carneiro et al, 2005). Information on method of processing negatively affected purchase intent of the respondents with the traditional method exhibiting less negative impact as compared to the industrial process of production.…”
Section: Main Sample and Segmentssupporting
confidence: 89%
See 3 more Smart Citations
“…Price, method of processing, and information on preservatives accounted for 34.54% of the respondents' purchase intents contributing 13.16%, 11.15%, and 10.23%, respectively (Table 2). Purchase intent decreased with an increase in price in accord with previous findings on fruits and vegetables (Van der Pol & Ryan, 1996), traditional cheeses (Souza Monteiro & Lucas, 2001), beef (Mesias, Escribano, de Ledesma, & Pulido, 2005), roasted peanuts (Nelson et al, 2005) and soybean oil (Carneiro et al, 2005). Information on method of processing negatively affected purchase intent of the respondents with the traditional method exhibiting less negative impact as compared to the industrial process of production.…”
Section: Main Sample and Segmentssupporting
confidence: 89%
“…This apparent lack-of-effect of the behavioral and demographic variables on segment membership indicates that the preference structure of concentrated yogurt consumers is largely shaped by the intrinsic attributes, chiefly sensory quality and fat levels, of the product under the experimental conditions. In the absence of taste as a factor, purchase intents, and the underlying preference structures, of food commodities have been shown to be markedly sensitive to the demographic and behavioral variables of consumers when analyzed by a combination of conjoint and multinomial logit models (Frank et al, 2001;Huang & Fu, 1995;Nelson et al, 2005). However, when tasting was incorporated into the study design, purchase decisions were found to be shaped primarily by taste qualities of products with demographic and behavioral variables exhibiting marginal effects when analyzed by conjoint designs allowing for modeling of intrinsic attributes of products and characteristics of individuals (Enneking, Neumann, & Henneberg, 2007).…”
Section: Demographic and Behavioral Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a review of the literature also supports using this attribute (see Table 1). This is the case of the works by Jaeger et al (2001) or Nelson et al (2005) on fruits, Sánchez et al ( , 2001a, Frank et al (2001) or Dagupen et al (2009) on vegetables, and Huddleston et al (2000), Orth & Firbasova (2003), Bernabéu et al (2007) or Menapace et al (2011) on other food products, e.g., honey, meat, eggs or organic food. Selecting levels for 'country of origin' responds to the goals of the present investigation too.…”
Section: Selection Of Attributes and Attribute Levelsmentioning
confidence: 99%